Maximizing place utility scheme in an urban neighborhood approximation of physical and perceptual environments - Lee, Lea Angela B. (2005)
On 1998, there was a strong argument concerning the declaration of Kidapawan into a city by virtue of Republic Act 8500 during Ramos Administration. Various issues surfaced among many sectors especially with regards to its political viewpoint. The issue on a greater internal revenue allotment (IRA) received from national administration has brought these sectors a statement that such conversion of political jurisdiction would entail corruption and pretenses of Kidapawan as a city. This, however, sometimes covered up main issues of urbanization concerning change and development. The researcher considered something beyond what has usually been surfacing in any declaration of town into city and finding, something irregardless of political problem. The approach to the study came to light from understanding various urban studies made after Kevin Lynch's success of defining image of a city. It is a research in the relationship between various persons' characteristics and their perceived environment (urbanized) characters in order to search for distinct meaning in terms of information, service, livability and aesthetics as towards defining a city. There are methods used in determining such structure that include mental maps and memory listings where it is essential to identify areas within the urbanized area that are highly critical of the need for environmental actions. Such actions that are considered are those changes that people make in their environment and in the study, modification and conservation of the identity landmark or areas is important to care about.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2005